1997
DOI: 10.1111/j.1365-2044.1997.170-az0305.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the nasal mask and the nasopharygeal airway in paediatric chair dental anaesthesia

Abstract: SummaryThis study compared the quality of anaesthesia and surgical access afforded by two techniques for the administration of anaesthesia during paediatric chair dental procedures. A total of 50 ASA 1 paediatric day case patients were randomly assigned to receive anaesthesia through either the traditional Goldman nasal mask or through a nasopharyngeal airway. Patients in the nasal mask group were judged to have significantly worse airway patency (p = 0.0001) and significantly more episodes of airway obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Holden et al 16 were the first one to compare the IOP changes using LMA and endotracheal tube and their observations as well as those of Lamb et al 17 revealed a significantly smaller increase in IOP using LMA both on placement and removal as compared to endotracheal intubation. Similar results were reported by Whitford et al 18 and Duman et al 19 The I-GEL is a new supraglottic device without an inflatable cuff, designed for use during anaesthesia. 20 It is a latex free, disposable device, made of a medical grade thermoplastic elastomer.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Holden et al 16 were the first one to compare the IOP changes using LMA and endotracheal tube and their observations as well as those of Lamb et al 17 revealed a significantly smaller increase in IOP using LMA both on placement and removal as compared to endotracheal intubation. Similar results were reported by Whitford et al 18 and Duman et al 19 The I-GEL is a new supraglottic device without an inflatable cuff, designed for use during anaesthesia. 20 It is a latex free, disposable device, made of a medical grade thermoplastic elastomer.…”
Section: Discussionsupporting
confidence: 83%
“…The rise in IOP after insertion of device was greater for the tracheal tube intubation group (18 In a similar study by Ismail et al, 22 they found that insertion of the I-GEL did not increase IOP. Insertion of an endotracheal tube increased IOP from 11.6±1.6 to 16.5±1.7 mmHg (p<0.001).…”
Section: Discussionmentioning
confidence: 75%
“…The nasopharyngeal airway has been used to provide an airway in these patients [3]. The airway is then connected directly to the breathing circuit.…”
Section: Discussionmentioning
confidence: 99%
“…Children having outpatient dental extractions under general anaesthesia have often been managed with a nasal mask [1,2] or nasopharyngeal airway [3]. A single dose of an intravenous induction agent has also been used with the extractions being performed during the recovery period.…”
mentioning
confidence: 99%
“…Induction and maintenance of anaesthesia was achieved using sevoflurane in nitrous oxide and oxygen. A nasal mask was used for maintenance of anaesthesia whenever possible, if a nasal airway had to be used this was noted [7].…”
Section: Methodsmentioning
confidence: 99%